EDUKASI DAN NEURORESTORASI PADA PASIEN PASCA STROKE DI RS EFARINA PEMATANGSIANTAR - Marolop Parlindungan Napitu; Isa Harpika Br. Ginting; Margaretha Togatorop (Yayasan Nusantara Hasana Berdikari, 2024)
This study presents an evaluation of a community service program, including education and neurorestoration, implemented at Efarina Hospital in Pematangsiantar for post-stroke patients. The program included the delivery of individually tailored written information, face-to-face discussion sessions, and telephone post-treatment support. The program was designed based on principles of patient education and neurorestoration support, which have been shown to increase patient confidence and satisfaction in accessing stroke-related information. The study combined an interactive educational approach with an emphasis on neurological rehabilitation, supporting the restoration of patient independence. Results from the community service program showed significant improvements in patients' ability to access information, a feeling of better informed care, and satisfaction with the information received. However, changes in general knowledge about stroke and psychosocial outcomes were not significant. This article reviews the methodology, results, and implications of the findings for the implementation of more intensive education and neurorestoration programs in the future.